The Role of Parents in Overcoming Juvenile Delinquency (Descriptive Study of Adolescents in Dilagusun Hamlet, Lamaksenulu Village Lamaknen District, Belu Regency) - Samrid Neonufa; Erni Raster Klau; Fredianus Dasi (Early Childhood Education Development and Studies (ECEDS), 2022)
ABSTRACT This thesis is entitled: "The Role of Parents in Overcoming Juvenile Delinquency (Descriptive Study of Adolescents in Dilagusun Hamlet, Lamaksenulu Village, Lamaknen District, Belu Regency)". The problems studied in this study are: What are the factors of juvenile delinquency?, what are the forms of juvenile delinquency and What is the Role of Parents in Overcoming Juvenile Delinquency. A descriptive study of Adolescents in Dilagusun Hamlet, Lamaksenulu Village, Lamaknen District, Kabupaten Speckle? The purpose of this study was to determine the factors that cause juvenile delinquency, forms of delinquency and how the role of parents in overcoming juvenile delinquency is a descriptive study of adolescent children in Dilagusun Hamlet, Lamaksenulu Village, Lamaknen District, Belu Regency. The research uses a qualitative descriptive study approach with the subjects of the Lamaksenulu Village community whose children are classified as naughty. Data was collected by using interview, observation and documentation techniques. The results showed: there are factors that cause juvenile delinquency in Lamaksenulu Village, namely: in the environment around teenagers they hang out with peers and influence each other and take actions that violate applicable norms and rules, and in that home environment children are often beaten by parents or by his own brother and and family economic factors that invite or force children to steal, here the child experiences mental retardation so that the child is easily influenced by the external environment or school environment with peers who invite him to take actions or forms. the form of delinquency, the child here is easily influenced. The forms of juvenile delinquency that occur in Dilagusun Hamlet, Lamaksenulu Village are where teenagers in the local area really belong to the naughty category, namely forms such as smoking, drinking liquor (laruh putih or sopi), shooting a friend's head using an air rifle. , sit together late into the night, steal parents' money and steal the neighbor's chicken. Parents play a role in preventing juvenile delinquency in Dilagusun Hamlet, Lamaksenulu Village, Lamaknen District, Belu Regency, according to the results of research and discussion it can be concluded that some of these roles include: (a). The role of parents as educators, (b) role as a driver, and (c) role as counselor (e) role of parents as supervisors and (f) role of parents as role models in overcoming juvenile delinquency in Dilagusun Hamlet, Lamaksenulu Village have been implemented. by local parents. And here the role of parents who have not been in the way of people in Lamaksenulu Village (d). The role of parents as friends is because communication between children and parents is not so good that the problems faced by children, their parents do not know what problems are faced by teenagers. Keywords: the role of parents, delinquency factor, forms of delinquency